Моделювання керованості колісних тракторів шляхом використання адаптивного рульового керування - Журавель, Дмитро Павлович; Бондар, Андрій Миколайович; Zhuravel, Dmytro; Bondar, Andrii (Запоріжжя : ТДАТУ, 2024)
UA: У статті проведено моделювання керованості колісних тракторів за допомогою адаптивного рульового керування. Виявлено, що найбільш важливі чинники, що впливають на керованість, включають швидкість руху, передаточне відношення рульового механізму, зовнішні фактори, чутливість рульового керування, тип рульового механізму і людський фактор. Розроблена математична модель адаптивного рульового керування дозволяє імітувати вплив збурюючих факторів на прямолінійність руху трактора, кут його повороту та геометричні параметри, а також швидкість руху, для забезпечення відповідності всім агротехнічним вимогам щодо обробки культурних рослин та якості виконання робіт. Наприклад, при виникненні збурюючих факторів під час міжрядної обробки кукурудзи, основним показником процесу є відхилення від прямолінійності на рівні 10 см при досягненні максимальної технологічної швидкості машинно-тракторного агрегату Vmax=4 м/с. EN: The article deals with the issue of controllability of wheeled tractors through the use of adaptive steering. It has been established that the most significant factors affecting the controllability of the machine-tractor unit are the speed of movement, the gear ratio of the steering mechanism, external disturbing factors, the sensitivity of the steering, the type of steering, as well as the human factor. A design scheme was developed and an experimental sample of adaptive steering control was developed, which provides a change in the gear ratio within 2...19, depending on the speed of movement of the machine-tractor unit when performing technological operations during the processing of any row crops grown in Ukraine. The developed mathematical model of adaptive steering control makes it possible to obtain process indicators that ensure compliance with all agrotechnical requirements for cutting cultivated plants and flip quality. For example, with the appearance of disturbing factors that occur during inter-row processing of corn, the main indicator of the process is a deviation from straightness of 10 cm when the machine-tractor unit reaches the maximum technological speed Vmax=4 m/s. Adaptive steering can be an effective method for improving the handling of wheeled tractors. This approach involves the use of various technologies and systems to adapt the operation of the steering mechanism depending on different operating conditions and the needs of the driver. The main possible directions for improving the controllability of tractors are as follows: electronic steering involves the use of electronics to control the steering mechanism, which allows implementing different modes of operation, in particular, adaptive control. Electronic systems can analyze various parameters, such as speed, type of surface, angle of inclination, and on this basis automatically adjust the response of the steering mechanism; built-in sensors such as gyroscopes, accelerometers, GPS and others can provide information about movement and environmental conditions. This information can be used for automatic adaptive control; using machine learning algorithms to analyze data and make management decisions. Machine learning models can learn from sensor data and driver experience to automatically adjust driving mode; Using power drives for independent control of each wheel. This can allow different wheels to move at different speeds or even in opposite directions to improve handling in different situations; using optimal control algorithms that automatically adjust to changing road conditions and tasks to maximize tractor control efficiency. When implementing such technologies, it is important to consider the training of drivers and the interaction of these systems with people to ensure safety and efficiency in real operating conditions.
Simulation of controlling wheel tractors using adaptive steering
Keywords: колісний трактор; рульове керування; моделювання процесу; передаточне відношення; автоматичний режим; швидкість руху; wheeled tractor; steering; process simulation; transmission ratio; automatic mode; speed of movement